(3JhVjM ChLg GNJdGa GdCbhGd aj eSGFd ef eYGedGJ GdCehGd (B/s - (3Hf Hjg, GdTjN YHO Gddg Hf GdTjN GdeMahXs ((3HjQhJ(B: s (3OGQ GHf MRe ddWHGYI hGdfTQ(B, s, 1998)
(3GdEjLGQ GdPj jfJgj HGdJedjc,ehba GdeDLQ ef JUQaGJ GdeSJCLQ ZjQ GdLGFRI TQYG,GdeTGQcI aj TQcGJ CUd fTGWgG MdGd EdG CfgG JJYGed HGdMQGe,GdJYGed eY TQcGJ Jbhe HCYeGd eTQhYI hJJYGed eY GdHfhc HGdahGFO,CMcGe GdfbhO GdhQbjI h JZjQ bjeI GdYedI,JHQFI GdPeI aj eSCdI GdQHG GdedeI,GdJYhjV Yf GdVQQ GdfGJL Yf JCNjQ SOGO GdOjhf GdeSJMbI,Mce GdTQY aj JYOjd eG JQJH HPeI GdeOjf ddOGFf aj MGdI GdJVNes
(3HHdjhZQGajG(B:(3U(B.5-6s
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdGSdGejs